A case report of recurrent C3 glomerulonephritis 18 months after renal transplantation. Issue 1 (December 2016) - Kakita, Hiroko; Miyake, Takafumi; Komiya, Toshiyuki; Tsukamoto, Tatsuo; Muso, Eri
Abstract Background The recurrence of glomerulonephritis (GN) is critical to the prognosis of long-term renal transplant graft survival. C3 GN is a rare GN with a poor prognosis, and there are only a few reports of recurrent cases after renal transplantation. We recently experienced a case highly suspected of C3 GN recurrence. Case presentation The patient was a 67-year-old male who had suffered from end-stage renal disease (ESRD) and started dialysis at the age of 60. His primary renal disease was unknown. At the age of 63, renal transplantation was successfully performed. His serum creatinine (Cr) level was maintained at 1.2 to 1.5 mg/dl, with no urinary protein or occult blood until 18 months after the transplant when urinary occult blood and protein became constant, along with an elevated Cr level at 1.5 to 1.6 mg/dl. The tentative diagnosis following a protocol biopsy at 36 months was dense-deposit disease. However, the pathological findings of an episode biopsy performed 1 year later, when his Cr level elevated to 2.0 mg/dl after varicella zoster virus reactivation, revealed no acute rejection but were compatible with C3 GN. Conclusions These findings are consistent with a previous report on recurrent C3 GN that revealed relatively rapid loss of graft function, contrasting well with slow progression occurring in the native kidney. This case is possibly the first report in Japan of recurrent C3 GN after renal transplantation.